Odpowiedzi

2010-04-13T18:08:44+02:00
Zredukuj wyrazy podobne .
a)b+a+r+b+a+p+a+p+a=4a+2b+2p+r
b)b-a-r-b-a-p-a-p-a =-4a-2b-2p-r
c)a+2b+3c-4c-5b-6a =-5a-3b-c
d)a³+2b-a²+3a²-10a³+5 =-9a³+2a²+2b+5
e)5x²-x²+y²+y-3-y+(-2)y²+5=4x²-y²-3
f)13x+7y-10x-4y+5y =3x+6y
g)90x+3y-x²-9×-9x-2y+x² =72x+y
1 5 1
2010-04-13T18:12:20+02:00
A)b+a+r+b+a+p+a+p+a=4a+2b+r+2p
b)b-a-r-b-a-p-a-p-a =-2b-4a-r-2p
c)a+2b+3c-4c-5b-6a =-5a+2b-c
d)a³+2b-a²+3a²-10a³+5 =-9a³+2b+2a²
e)5x²-x²+y²+y-3-y+(-2)y²+5=4x²-y²-3
f)13x+7y-10x-4y+5y =3x+8y
g)90x+3y-x²-9×9x-2y+x² =9x+y



Pozdrawiam;)
3 3 3